The immunoprotective Anaplasma marginale major surface protein 2 is encoded by a polymorphic multigene family. - Palmer, G H (1994)
An Anaplasma marginale Florida msp-2 gene was cloned and expressed in Escherichia coli. Pulsed-field gel electrophoresis and Southern blot analysis revealed the presence of multiple msp-2 gene copies that were widely distributed throughout the chromosomes of all three strains examined. Genomic polymorphism among copies was greatest in the 5' end of msp-2 but also occurred in 3' regions. The presence of gene-copy-specific epitopes was indicated by the reactivity of the cloned msp-2 copy with some, but not all, monoclonal antibodies that bound native MSP-2. Multiple antigenically distinct MSP-2 molecules were expressed within strains and were coexpressed by individual A. marginale organisms. These results suggest that expression of polymorphic msp-2 gene copies is responsible for the significant percentages of A. marginale organisms within strains that do not react with individual anti-MSP-2 monoclonal antibodies. Sequence analysis revealed highly significant MSP-2 homology with two rickettsial surface proteins, A. marginale MSP-4 and Cowdria ruminantium MAP-1. Immunization with MSP-4 has been shown to induce protective immunity in a manner similar to that of immunization with MSP-2. These findings support the hypothesis that A. marginale surface proteins are targets of protective immune responses but are antigenically polymorphic.